Application of Gamma Radiation Doses on Two Varieties of Sugar Palm (Arenga pinnata MERR.) To Obtain The Best Growth Rate With Drought-Stressed Planting Media - Marwah, Mahakarya; Andi Apriany Fatmawaty; Rohmawati, Imas; Abdul Hasyim Sodiq (Jurnal Agroekoteknologi Terapan, 2025)
Aren (Arenga pinnata Merr.) is a plant with high economic value. To obtain superior seeds, gamma radiation can be used, which has been proven to increase genetic variation and support optimal growth. This study aims to determine the effect of gamma radiation dosage and two varieties of aren on the optimal growth rate of aren (Arenga pinnata Merr.) using a drought stress growing medium. This study used a factorial Randomised Block Design (RBD). The first factor was the gamma radiation dose (B), consisting of 5 levels: 0 Gy, 4 Gy, 6 Gy, 8 Gy, and 10 Gy. The second factor was the palm variety (V), consisting of 2 levels: Parasi (V1) and local Lebak (V2). The results showed that the gamma ray dose of B2 or 6 Gy had the best effect on plant height, leaf width, number of leaves, and leaf greenness. The aren palm varieties (V) Parasi (V1) and local Lebak (V2) did not have a significant effect on plant height, leaf width, number of leaves, and leaf greenness. There was no interactive effect between gamma radiation dose treatment (B) and sugar palm variety (V) on plant height, leaf width, number of leaves, and leaf greenness. Keywords: Aren (Arenga pinnata Merr.), gamma rays, palm varieties